Analysis of the synchronization error measurement via non-collinear cross-correlation. (29th April 2015) - Mu, J.; Wang, X.; Jing, F.; Zhu, Q.H.; Su, J.Q.; Zhang, J.W.
Abstract The method for measuring synchronization error of ultra-short pulses was introduced based on the principle of non-collinear cross-correlation. The analytical expression for the measurement was deduced according to the cross-correlation signal. The influences of angular error on the measurement were analyzed by simulated experiments. The incident angle and the angular error tolerance were both required to be considered and determined for the synchronization error measurement of ultra-short pulses. The results provide a theoretical basis for the measurement and control of the synchronization error in the coherent beam combination, plasma parameter diagnosis, etc.